1987
DOI: 10.1071/ea9870679
|View full text |Cite
|
Sign up to set email alerts
|

Increasing wheat yields in north-eastern Victoria by liming and deep ripping

Abstract: Wheat grain yields, dry matter production and yield components were measured in a field experiment in north-eastern Victoria over 5 seasons where lime application and deep ripping had been carried out. The soil at the site was strongly acid (pHw 5.2 at 0-1 0 cm) and had a dense hardpan at 7.5- 17.5 cm depth. Grain yields (control yields 1981-85: 1.34, 0.25, 1.64, 2.36, 2.09 t ha-1) were increased each year by both lime (31-103% range) and deep ripping (11- 41% range), but the application of some lime was neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…It has also received great acceptance by the farming community. There are several reasons for this: besides reducing P losses, there is usually a yield benefit associated with liming (Coventry et al, 1987), which increases the cost-effectiveness of the method. However, there are still unanswered questions related to structure liming that require more field studies (e.g., to clarify the effect of structure liming on P leaching as a function of available soil P content alone and in combination with different clay contents in soil).…”
Section: Reflections On the Use Of Best Management Practices To Reducmentioning
confidence: 99%
“…It has also received great acceptance by the farming community. There are several reasons for this: besides reducing P losses, there is usually a yield benefit associated with liming (Coventry et al, 1987), which increases the cost-effectiveness of the method. However, there are still unanswered questions related to structure liming that require more field studies (e.g., to clarify the effect of structure liming on P leaching as a function of available soil P content alone and in combination with different clay contents in soil).…”
Section: Reflections On the Use Of Best Management Practices To Reducmentioning
confidence: 99%
“…Higher use of N fertilizer and higher removal of cations when using the wheat for both forage and grain compared to grain only may accelerate acidification, especially when soils are not limed. Although numerous studies have investigated the effects of lime on grain yields of various crops, only a few studies have reported how the biomass production of wheat is affected by soil pH and liming rates (2,9). The objectives of the present work were to: (i) determine the effect of lime applications on soil pH; (ii) examine the effect of liming on the yield and quality of winter wheat forage; and (iii) examine the economics of liming winter wheat for forage.…”
Section: Introductionmentioning
confidence: 99%
“…Deep tillage is one way to treat soil compaction to promote deep rooting (e.g. Coventry et al, 1987). However, crop responses to deep tillage have often been variable and the soil may recompact to densities equal to or even greater than before (Mead and Chan, 1988).…”
Section: Introductionmentioning
confidence: 99%